Design of Automatic Assembly Station for Industrial Vehicles Parts - Jenis Jozef (Sciendo, 2021)
Automated production and assembly lines can be considered a crucial factor in accelerating the production processes and achieving the maximum financial savings. In particular, specialized single-purpose machines can significantly reduce production or assembly time. The submitted article presents a design of a single-purpose device that is used for the automated assembly of a roller bush with a screw. These components are then used for construction and agricultural vehicles to attach other components. Naturally, the design of this specific device is more demanding in terms of time consumption, precision, detail and initial investment than similar less complicated all-purpose devices. Nevertheless, single-purpose devices turn out to be a better option in the sense of quality and profit both in the long-term and high-capacity projects, such as automotive industry, agricultural and construction machinery. The best alternative was selected from several proposals using the evaluation method. The assembly machine was designed and optimized using Computer Aided Design systems and Finite Element Method analyses. The resulting equipment was used in practice, where it significantly increased the productivity and production efficiency.